2001
DOI: 10.1053/jhep.2001.27564
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new hepatitis B triple-antigen vaccine in inadequate responders to current vaccines

Abstract: In this double-blind, randomized, controlled study, healthcare professionals with a history of inadequate response to currently available single-antigen hepatitis B vaccines confirmed by measuring hepatitis B surface antibody titer before entry to the study were revaccinated with a 20-g dose either of a novel triple-antigen (S, pre-S1, and pre-S2) recombinant vaccine or of a present single-antigen (S only) vaccine. Hepatitis B surface antibody titers were measured 8 weeks' post revaccination. A total of 925 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 21 publications
0
36
1
2
Order By: Relevance
“…Studies using overlapping peptides revealed that the pre-S region was important for eliciting T cell responses and, thus, help to improve the immunogenicity of the PreS/S vaccine (60). However, the enhanced immunogenicity was only observed for mammalian cell-produced PreS/S vaccines (57), not for yeastderived PreS/S vaccines (58,59), suggesting that glycosylation might also play a role in the improved immunogenicity. The expected high cost of the mammalian-produced vaccine will limit its clinical application.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies using overlapping peptides revealed that the pre-S region was important for eliciting T cell responses and, thus, help to improve the immunogenicity of the PreS/S vaccine (60). However, the enhanced immunogenicity was only observed for mammalian cell-produced PreS/S vaccines (57), not for yeastderived PreS/S vaccines (58,59), suggesting that glycosylation might also play a role in the improved immunogenicity. The expected high cost of the mammalian-produced vaccine will limit its clinical application.…”
Section: Discussionmentioning
confidence: 95%
“…HBsAg-pulsed DCs, a cellbased vaccine, was reported to induce anti-HBs Abs in HBsAg vaccine nonresponders (54). The pre-S-containing HBsAg (PreS/ S) vaccine, with addition of the pre-S1 and pre-S2 sequences to the S protein, helped to circumvent immune nonresponsiveness to HBsAg in B10.M mice (55,56) and in several human clinical trials (57)(58)(59). Studies using overlapping peptides revealed that the pre-S region was important for eliciting T cell responses and, thus, help to improve the immunogenicity of the PreS/S vaccine (60).…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, recombinant hepatitis B -L62 +/+ S113T T126I, T143S --L119 -/+ K24R,Q56P,I57T,C64S, S113T T126I, T143S --vaccines that include pre-S1 and pre-S2 regions currently unavailable. However, this new triple-antigen vaccine is more efficient than the single-antigen vaccine, 20,21 and prevents infection from vaccine-escape mutants. 22 The triple-antigen vaccine should be considered in our study area where the prevalence of anti-HBs remains insufficient among children.…”
Section: Discussionmentioning
confidence: 99%
“…18 A high-antigen-content vaccine with a novel adjuvant (MPL plus alum; AS04) is also associated with higher seroprotective rates and geometric mean antibody levels in nonresponders. 12,18 Other novel vaccines, including a triple-antigen HBsAg vaccine (S, pre-S1, pre-S2) 13,17 and a DNA vaccine, 16 have demonstrated improved efficacy in nonresponders. Multisite revaccination with HBsAg-Eng vaccine via the intradermal route can also induce seroconversion in some nonresponders.…”
Section: Demographics and Participant Dispositionmentioning
confidence: 99%